Choice of a machine-building enterprise client with limited production capacities - Pistunov, Ihor (My University, 2024)
The limitation of production resources with a significant portfolio of orders forces manufacturers to choose the most profitable among all orders. Let's consider the solution of this problem for a machine-building enterprise that manufactures large-sized structures. For this, statistics were collected from 80 orders that were previously fulfilled by this enterprise on nine factors, indicating their conventional designations.
Keywords: machine-building enterprise; машинобудівне підприємство; large-sized structures; великогабаритна конструкція; integer simplex method; цілочисельний симплексний метод